PENERAPAN MODEL PROBLEM BASED LEARNING BERBASIS BUDAYA MELAYU UNTUK MENINGKATKAN RESILIENSI SISWA PADA PEMBELAJARAN MATEMATIKA - Aulia Hutagalung, Siti Nur'ibni; Sukmawarti, Sukmawarti; Hidayat, Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the application of the Malay culture-based Problem-Based Learning (PBL) model to improve student resilience in mathematics learning. The background of this study is the low level of student resilience, reflected in a lack of perseverance, low self-efficacy, and an inability to manage emotions when facing difficulties in learning mathematics. Malay culture, rich in values such as mutual cooperation, perseverance, and respect, can provide a learning context that strengthens students' affective aspects. This study used a qualitative approach to describe the learning process and changes in student attitudes/responses, while a quantitative approach was used to measure resilience improvements through a questionnaire. Data were collected through questionnaires, observations, interviews, and documentation. Quantitative data were analyzed descriptively by comparing pretest and posttest results, while qualitative data were analyzed through reduction, presentation, and conclusions. The results showed that the application of the Malay culture-based PBL model significantly improved student resilience. In addition, students became more active, confident, and able to work collaboratively in groups. Contextual learning that emphasizes local cultural values has proven effective in creating a learning environment that supports the development of character and student learning resilience.